(untitled) (Journal of the College of Basic Education, 2025)
Five yeast isolates were obtained from spoiled fruits and subjected to multiple purification processes until their purity was confirmed microscopically. Then, they were subjected to primary screening to identify the isolates with high growth density. The results showed that isolate (Y1) were distinguished by observing the growth density on the medium used with different incubation temperatures. To diagnose the selected isolate obtained from the primary screening stage, tests related to phenotypic, cultural, physiological, and biochemical characteristics were conducted, all of which showed that isolate Y1 belonged to Saccharomyces cerevisiae, as the results obtained matched several scientific references (diagnostic keys) in this field. The results of yeast diagnosis using the Vitek device also showed that the isolate under study belongs to S. cerevisiae. The immunodiffusion test of the yeast isolate showed that Y1 and its antiserum have an immunological relationship, as it was noted that the titer of the antiserum to the yeast isolate was (8/1). Cross-reactivity was observed between the local yeast isolate Y1 and the commercial yeast with the antiserum to the Y1 yeast isolate, which indicates the identity of the antigenic determinants between both the local yeast Y1 and the commercial yeast. The results also showed the presence of inhibitory activity of the local yeast filtrate Y1 against pathogenic enteric bacteria isolated from stool samples of children under five years of age who were infected with acute bloody and watery diarrhea, as the diameters of the inhibition zone for 100 µL (1 mg/mL) of the filtrate of these yeast cells reached 21, 18, and 16 mm for each of Escherichia coli, Salmonella typhimurium, and Shigella flexneri.